2019
DOI: 10.1016/j.jobcr.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glypican-3 expression in benign and malignant salivary gland tumors

Abstract: Introduction: Glypican-3 (GPC3) is involved in regulation of cell proliferation and morphogenesis. It is abundant in embryonic tissue, but limited in most adult tissues. GPC3 deletion or mutation can disturb the balance between cell apoptosis and proliferation, which may result in tumorigenesis. This study aimed to investigate the GPC3 expression in salivary gland tumors (SGTs) and the adjacent non-neoplastic tissues. Methods: This study reviewed 50 samples of salivary tumors from the archive of Khalili Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…All positive staining were evaluated using a semi-quantitative scoring system for the percentage of positively stained cancer cells as follows: occasional staining but <10% were considered negative, 10%–40% were considered mild, 40%–70% were scored moderate, and >70% were considered intense staining. [ 17 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All positive staining were evaluated using a semi-quantitative scoring system for the percentage of positively stained cancer cells as follows: occasional staining but <10% were considered negative, 10%–40% were considered mild, 40%–70% were scored moderate, and >70% were considered intense staining. [ 17 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Previous studies have shown that the patients with BRCA1/2 mutation carriers are excellent cases for therapies, such as the poly (ADP) ribose polymerase inhibitor. [ 17 ] IHC is a low-cost and efficient method;[ 39 ] therefore, it can serve as a screening test for detection of BRCA1/2 dysfunction in salivary gland tumor. The knowledge of the spectrum of mutations can provide more efficient protocol for screening and therapeutic strategy.…”
Section: Onclusionsmentioning
confidence: 99%
“…Endometriosis, like a malignant tumor, is invasive and capable of forming blood vessels at the distal end, thus leading to endometriosis or even metastasis to the lungs and nasal cavity. [15,16] MTA1 is highly expressed in many malignant tumors, especially epithelial-derived endometrial cancer, [14] breast cancer, [17] gastrointestinal cancer, [18] prostate cancer, [19] salivary gland carcinoma, [20] and other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…SGTs consist of a spectrum of tumors with different biological behaviors and diverse clinical pathophysiology. The most common SGT is pleomorphic adenoma and the most common malignant SGTs are MEC (mucoepidermoid carcinoma) and ACC (adenoid cystic carcinoma) [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%